Ionotropic and Metabotropic Proton-Sensing Receptors Involved in Airway Inflammation in Allergic Asthma - Aoki, Haruka (Hindawi Publishing Corporation, 2014)
An acidic microenvironment has been shown to evoke a variety of airway responses, including cough, bronchoconstriction, airway hyperresponsiveness (AHR), infiltration of inflammatory cells in the lung, and stimulation of mucus hyperproduction. Except for the participation of transient receptor potential vanilloid-1 (TRPV1) and acid-sensing ion channels (ASICs) in severe acidic pH (of less than 6.0)-induced cough and bronchoconstriction through sensory neurons, the molecular mechanisms underlying extracellular acidic pH-induced actions in the airways have not been fully understood. Recent studies have revealed that ovarian cancer G protein-coupled receptor 1 (OGR1)-family G protein-coupled receptors, which sense pH of more than 6.0, are expressed in structural cells, such as airway smooth muscle cells and epithelial cells, and in inflammatory and immune cells, such as eosinophils and dendritic cells. They function in a variety of airway responses related to the pathophysiology of inflammatory diseases, including allergic asthma. In the present review, we discuss the roles of ionotropic TRPV1 and ASICs and metabotropic OGR1-family G protein-coupled receptors in the airway inflammation and AHR in asthma and respiratory diseases.